2000
DOI: 10.1042/bst0280969
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic oil palm: production and projection

Abstract: Oil palm is an important economic crop for Malaysia. Genetic engineering could be applied to produce transgenic oil palms with high value-added fatty acids and novel products to ensure the sustainability of the palm oil industry. Establishment of a reliable transformation and regeneration system is essential for genetic engineering. Biolistic was initially chosen as the method for oil palm transformation as it has been the most successful method for monocotyledons to date. Optimization of physical and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Taken together, it took nearly 2 years to regenerate transformed oil palm plantlets that were of approximately 15 cm in height from the day of transformation. Previously, Parveez et al (2000) reported that it took almost 3 years to generate Basta-resistant transgenic oil palm plantlets after transformation using biolistic. The plantlets obtained were all phenotypically normal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, it took nearly 2 years to regenerate transformed oil palm plantlets that were of approximately 15 cm in height from the day of transformation. Previously, Parveez et al (2000) reported that it took almost 3 years to generate Basta-resistant transgenic oil palm plantlets after transformation using biolistic. The plantlets obtained were all phenotypically normal.…”
Section: Resultsmentioning
confidence: 99%
“…Even though regeneration of transgenic oil palm from EC was first reported more than 10 years ago, the transformation efficiencies were rather low, between 0.7 and 1.5% only (Parveez et al, 2000; Masli et al, 2009). These reports used EC as target tissue and the efficiency was calculated based on percentage of transient over stable transformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating methylation patterns of these target genes will pave the way for understanding the epigenetic mechanisms underlying the induction and maintenance of somaclonal variation in oil palm regenerants. Since the initial transformation of oil palm with a marker gene has been reported by Parveez et al (2000), genetic engineering in oil palm is progressing at the slow pace imposed by public acceptance, biosafety issues, and the genetic complexity of desired traits (from the production of bioplastics to the introduction of resistance to major pasts and diseases). Subhi et al (2010) have recently identified the ubiquitin extension protein (uep1) gene as a constitutively expressed gene in oil palm.…”
Section: Biotechnologies Already Impacts Oil Palm Productivitymentioning
confidence: 99%
“…Various genetically modified plants are being developed, such as shorter palms that can produce fruits for longer than 25 years, but commercial plantings are unlikely before 2020 (Parveez et al 2000). By May 2008, the first phase of sequencing the oil palm genome was complete, which may provide significant future improvements in both quality and production (Crowley 2008).…”
mentioning
confidence: 99%